Model Tests for the Effect of Random Waves on the Hydrodynamic Forces on Rigid Vertical Cylinders - Kurian, V.J. (2013)
Abstract— Evaluation of accurate hydrodynamic forces on slender pipes has great significance in designing offshore structures. For the analysis and design of jacket platforms made up of small diameter tubular members, consultants use Morison’s equation, where the wave forces are calculated using drag (CD) and inertia (CM) coefficients. The hydrodynamic coefficients used by consultants are constant values, although CD and CM are dynamic coefficients that depend on Keulegan Carpenter number (KC) and Reynolds’s number (Re). This paper provides the preliminary results of model tests on rigid vertical cylinders with different pipe diameters subjected to random waves. The experimental data are derived from 1:70 scale model tests in which the hydrodynamic forces acting on individual tubular pipes were investigated in the wave tank. The hydrodynamic forces on the model were measured using aluminium block load sensors. The model pipe diameters used for the preliminary tests were 22 mm, 34 mm and 42 mm, and the effects of random waves on the magnitude of prototype hydrodynamic forces were analyzed in terms of power spectral density. Keywords — Dynamic responses, Inertia coefficient, Drag coefficient, Malaysian locations, Morison equation.